Brain region-specific genome-wide deoxyribonucleic acid methylation analysis in patients with Alzheimer’s disease - Ren, Gang; Song, Shan; Zhang, Sheng-Xiao; Liu, Yan; Lv, Yan; Wang, Yan-Hong; Zhao, Rong; Li, Xin-Yi (Frontiers in Molecular Neuroscience, 2023)
Objective: Alzheimer’s disease (AD) is a neurodegenerative disease characterized by neuropathology and cognitive decline and associated with age. The comprehensive deoxyribonucleic acid methylation (DNAm)-transcriptome profile association analysis conducted in this study aimed to establish whole-genome DNAm profiles and explore DNAm-related genes and their potential functions. More appropriate biomarkers were expected to be identified in terms of AD. Methods: Illumina 450KGSE59685 dataset AD (n = 54) and HC (n = 21) and ribonucleic-acid-sequencing data GSE118553 dataset AD patients (n = 84) and HCs (n = 52)were obtained from the gene expression omnibus database before a comprehensive DNAm-transcriptome profile association analysis, and we performed functional enrichment analysis by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses(KEGG). Three transgenic mice and three wild-type mice were used to validate the hub genes. Results: A total of 18,104 DNAm sites in healthy controls (n = 21) and AD patients (n = 54) were surveyed across three brain regions (superior temporal gyrus, entorhinal cortex, and dorsolateral prefrontal cortex). With the addition of the transcriptome analysis, eight hypomethylated-related highly expressed genes and 61 hypermethylated-related lowly expressed genes were identified. Based on 69 shared differentially methylated genes (DMGs), the function enrichment analysis indicated Guanosine triphosphate enzymes (GTPase) regulator activity, a synaptic vesicle cycle, and tight junction functioning. Following this, mice-based models of AD were constructed, and five hub DMGs were verified, which represented a powerful, disease-specific DNAm signature for AD. Conclusion: The results revealed that the cross-brain region DNAm was altered in those with AD. The alterations in DNAm affected the target gene expression and participated in the key biological processes of AD. The study provides a valuable epigenetic resource for identifying DNAm-based diagnostic biomarkers, developing effective drugs, and studying AD pathogenesis.